1986
DOI: 10.1001/archotol.1986.03780100038004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Uptake of Salicylate in Serum, Cerebrospinal Fluid, and Perilymph

Abstract: \s=b\After intraperitoneal administration of salicylate in anesthetized rats and guinea pigs, we found that salicylate levels in perilymph (PL) are closely related to both drug levels in cerebrospinal fluid (CSF) and in serum, with higher levels systematically observed in PL than in CSF. Further analysis suggests that salicylate is not passively transported into PL across CSF but, rather, is transported from blood directly to PL. The time course of salicylate uptake in rats reveals maximum levels at 1\m=1/2\ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 23 publications
6
42
0
Order By: Relevance
“…Although the K 1/2 we observed was 1.6 mM, effects on the sensor/motor were observed in the hundred micromolar range. It has been shown that the perilymphatic salicylate concentration, which induces tinnitus and hearing loss in the rat, is near 400 M (Jastreboff et al, 1986). Therefore, the data we obtain in vitro are in accord with in vivo results.…”
Section: Discussionsupporting
confidence: 86%
“…Although the K 1/2 we observed was 1.6 mM, effects on the sensor/motor were observed in the hundred micromolar range. It has been shown that the perilymphatic salicylate concentration, which induces tinnitus and hearing loss in the rat, is near 400 M (Jastreboff et al, 1986). Therefore, the data we obtain in vitro are in accord with in vivo results.…”
Section: Discussionsupporting
confidence: 86%
“…This 5-HT-induced enhancement of GABAergic sIPSCs very possibly results from the increased spontaneous firing of presynaptic GABA neurons in the presence of 5-HT. SS at 1.4 mM, a typical concentration found in the cerebrospinal fluid of animal models with SS-induced tinnitus (Jastreboff et al, 1986(Jastreboff et al, , 1988Silverstein et al, 1967), likely suppresses the 5-HTinduced enhancement of GABAergic sIPSCs (Fig. 4) through depressing spontaneous action potentials in presynaptic GABA neurons since TTX exerted a similar effect as SS did (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Available evidence suggests that SS may produce tinnitus through directly targeting neurons and synapses in the central auditory system. Such lines of evidence include: (1) salicylate concentrations in the cerebrospinal fluid of animal models with behavioral manifestation of tinnitus induced by SS can reach a high level up to 1-2 mM (Deer and Hunter-Duvar, 1982;Jastreboff et al, 1986;Silverstein et al, 1967); (2) in a brain slice preparation, SS significantly reduces evoked inhibitory postsynaptic currents in rat auditory cortex (Wang et al, 2006) and changes the spontaneous activity of inferior colliculus neurons (Basta and Ernst, 2004); (3) treatment with SS injection increases the amplitude of local field potentials recorded from the auditory cortex of unanaesthetized rats (Yang et al, 2007) and changes spontaneous firing rate in the secondary auditory cortex of anesthetized cats (Eggermont and Kenmochi, 1998;Ochi and Eggermont, 1996); (4) animal microPET imaging shows that SS increases metabolic activity in the central auditory structures (Paul et al, 2007). These lines of evidence prompt a need to further explore how SS targets the central auditory system at a cellular and synaptic level in order to understand the exact neural mechanisms in SS-induced tinnitus.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no models of cochlear function which can quantitatively explain otoacoustic emissions and non-linear phenomena, it is possible to provide a qualitative explanation for most of these observations if the OHC motor alone is affected, even though there are indications that further ototoxic effects may arise indirectly through salicylate effects on cochlear blood flow (Didier, Miller & Nuttall, 1993). There is ample evidence to suggest that aspirin ingestion leads to elevated serum salicylate levels, in some cases in the millimolar range (Jastreboff, Hansen, Sasaki & Sasaki, 1986). These levels are not cleared rapidly and may distribute between serum, cerebrospinal fluid and perilymph.…”
Section: Resultsmentioning
confidence: 99%